2013
DOI: 10.1093/annonc/mdt107
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab alone or in combination with radiotherapy in metastatic castration-resistant prostate cancer: results from an open-label, multicenter phase I/II study

Abstract: In mCRPC patients, ipilimumab 10 mg/kg ± radiotherapy suggested clinical antitumor activity with disease control and manageable AEs. Two phase III trials in mCRPC patients evaluating ipilimumab 10 mg/kg ± radiotherapy are ongoing. ClinicalTrials.gov identifier: NCT00323882.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
337
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(348 citation statements)
references
References 44 publications
6
337
1
4
Order By: Relevance
“…58 Seventy patients with metastatic, castrate-resistant prostate cancer enrolled on that trial, and 41 received RT. The delivery of palliative-dose RT before ipilimumab was identified as safe; and all AEs, including irAEs, were unchanged with the combination therapy at both 3 mg/kg and 10 mg/kg of ipilimumab.…”
Section: Ctla-4 Inhibition With or Without Single-fraction Palliativmentioning
confidence: 99%
“…58 Seventy patients with metastatic, castrate-resistant prostate cancer enrolled on that trial, and 41 received RT. The delivery of palliative-dose RT before ipilimumab was identified as safe; and all AEs, including irAEs, were unchanged with the combination therapy at both 3 mg/kg and 10 mg/kg of ipilimumab.…”
Section: Ctla-4 Inhibition With or Without Single-fraction Palliativmentioning
confidence: 99%
“…35 Subsequent case reports and phase II studies have further increased the research interest, with these initial results suggesting that RT in combination with immunoregulatory agents may lead to "abscopal" responses in some patients, providing optimism that RT can enhance the systemic antiimmune response. 36,37 The underlying principle is that local RTinduced ICD and antitumour immune responses need to be augmented with the addition of immunoregulatory agents which enhance the local and systemic immune response by overcoming the immunosuppressive nature of the local tumour environment, leading to systemic specific antitumour immunity and increasing the possibility of abscopal effects (Figure 1). …”
Section: Enhancing the Immunogenic Potential Of Stereotactic Ablativementioning
confidence: 99%
“…CTLA-4 has been shown to be up regulated upon T cell activation, in order to diminish this response. In the mCRPC setting, ipilimumab was tested in a phase I/II trial, where patients received ipilimumab in several dosing schedules plus radiation to a single bone metastasis (24). Results of this trial showed that ipilimumab has antitumor activity with tumor control and manageable toxicities.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%